2020
DOI: 10.3329/sja.v18i1.48381
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Lentil as Affected by Reduced Tillage and Mechanical Seeding

Abstract: Generally, lentil seeds are sown following the traditional farming practice with 3-4 numbers of ploughing combined with broadcasting method in lentil growing countries. This is time consuming and costly. The objective of this study was to evaluate the lentil performance as affected by different mechanical seeding system as well as seeding device. There were seven different treatments of which two tillage systems like i) broadcasting after4 times tillage (CT) and ii) broadcasting after tillage with two wheeler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The lower in yield under zero-tillage may be due to greater weed infestation and bulk density, which negatively affect the uptake of nutrients and water. Zaman and Islam (2020) reported that zero tillage decreased by 9.67 % seed yield compared to conventional tillage [10].…”
Section: Grain Yieldmentioning
confidence: 99%
“…The lower in yield under zero-tillage may be due to greater weed infestation and bulk density, which negatively affect the uptake of nutrients and water. Zaman and Islam (2020) reported that zero tillage decreased by 9.67 % seed yield compared to conventional tillage [10].…”
Section: Grain Yieldmentioning
confidence: 99%
“…Strip tillage technologies are more viable in drought stress areas where seeding operations and initial plant establishment can be carried out with residual soil moisture available immediately after monsoon rice harvest (Bell and Johansen, 2009). Many research reports suggest that strip tillage lentil cultivation is possible (Zaman et al, 2019 and2020). Lentils are placed in first position according to area coverage (40% of total pulse area) and production (45% of total pulse production).…”
Section: Introductionmentioning
confidence: 99%